ScaleXdesign - competition - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The project is ready for scaling. A 5 year budget with break even in year 3 has been developed. Willlingnees to pay and how to be established as Social Enterprise and interaction with Tech companies in Vietnam to be explored.